Understanding the Emerging Link Between Circadian Rhythm, Nrf2 Pathway, and Breast Cancer to Overcome Drug Resistance - Bevinakoppamath, Supriya; Ramachandra, Shobha Chikkavaddaragudi; Yadav, Anshu Kumar; Basavaraj, Vijaya; Vishwanath, Prashant; Prashant, Akila (Frontiers in Pharmacology, 2022)
The levels of different molecules in the cell are rhythmically cycled by the molecular clock present at the cellular level. The circadian rhythm is closely linked to the metabolic processes in the cells by an underlying mechanism whose intricacies need to be thoroughly investigated. Nevertheless, Nrf2 has been identified as an essential bridge between the circadian clock and cellular metabolism and is activated by the by-product of cellular metabolism like hydrogen peroxide. Once activated it binds to the specific DNA segments and increases the transcription of several genes that play a crucial role in the normal functioning of the cell. The central clock located in the suprachiasmatic nucleus of the anterior hypothalamus synchronizes the timekeeping in the peripheral tissues by integrating the light-dark input from the environment. Several studies have demonstrated the role of circadian rhythm as an effective tumor suppressor. Tumor development is triggered by the stimulation or disruption of signaling pathways at the cellular level as a result of the interaction between cells and environmental stimuli. Oxidative stress is one such external stimulus that disturbs the prooxidant/antioxidant equilibrium due to the loss of control over signaling pathways which destroy the bio-molecules. Altered Nrf2 expression and impaired redox balance are associated with various cancers suggesting that Nrf2 targeting may be used as a novel therapeutic approach for treating cancers. On the other hand, Nrf2 has also been shown to enhance the resistance of cancer cells to chemotherapeutic agents. We believe that maximum efficacy with minimum side effects for any particular therapy can be achieved if the treatment strategy regulates the circadian rhythm. In this review, we discuss the various molecular mechanisms interlinking the circadian rhythm with the Nrf2 pathway and contributing to breast cancer pathogenesis, we also talk about how these two pathways work in close association with the cell cycle which is another oscillatory system, and whether this interplay can be exploited to overcome drug resistance during chemotherapy.